ANIMADVERSION OF THE TOTALITARISM AND ITS KINDS (BOLSHEVISM AND FASCISM) BY UKRAINIAN RADICAL PARTY – UKRAINIAN SOCIAL-RADICAL PARTY - Міщук, А. І.; Міщук, М. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is devoted of the animadversion of the Ukrainian Radical Party – Ukrainian Social-Radical Party, one of the most active in political respect parties’ in the life of the Western-Ukrainian land, Soviet Bolshevism and Nazi Germany, which were considered radical only as manifestations and types of totalitarianism. Shown that between communism and fascism party members conducted parallel because both regimes, in their opinion, were characterized by the presence of a powerful state apparatus, the dictatorship of one person, the lack of democratic freedoms, the monopoly of one party and the use of violent methods.